The Effect of Merchant Characteristics and Religious Tour Visits as a Moderating Variable to Merchant Revenues (Study in Sunan Ampel Religious Tourism Area, Surabaya) - Lestari, Alfi Muflikhah; Multifiah, Multifiah; Hoetoro, Arif (Journal of Indonesian Tourism and Development Studies, 2018)
This study aims to determine the influence of merchant characteristics based on age, education, capital, years in business and labor to the income of merchants and to know the effect of religious tourism as moderating variable that influences the Sunan Ampel religious tourism area of Surabaya. This research used simple random sampling technique with 70 merchants as respondent. Data were analyzed using moderation regression with interaction method. The results showed age, capital and labor have a significant effect on the merchant's income while the years in business and education have no significant effect on the merchant's income. The result of research on religious tourism visit as moderating variable shows religious tourism visit has a moderating effect on the relationship of age, capital and business time to the merchant's income. On the other hand, this variable has no moderating effect on the relation of labor and education to the merchant's income.Keywords: age, capital, education, labor, religious tourism, the income of merchants, years in business.